Language in the Digital Era. Challenges and Perspectives - Hansen, Gyde (De Gruyter, 2016)
This collected volume brings together the contributions of several humanities scholars who focus on the evolution of language in the digital era. The first part of the volume explores general aspects of humanities and linguistics in the digital environment. The second part focuses on language and translation and includes topics that discuss the digital translation policy, new technologies and specialised translation, online resources for terminology management, translation of online advertising, or subtitling. The last part of the book focuses on language teaching and learning and addresses the changes, challenges and perspectives of didactics in the age of technology. Each contribution is divided into several sections that present the state of the art and the methodology used, and discuss the results and perspectives of the authors. The book is recommended to scholars, professionals, students and anyone interested in the changes within the humanities in conjunction with technological innovation or in the ways language is adapting to the challenges of today's digitized world.